Existence of Periodic Positive Solutions for Abstract Difference Equations. (31st July 2011) - Kang, Shugui; Cui, Yaqiong; Guo, Jianmin
Abstract : We will consider the existence of multiple positive periodic solutions for a class of abstract difference equations by using the well-known fixed point theorem (due to Krasnoselskii).